Emotional and behavioral problems seen among a group of children and adolescents living in a refugee camp in Turkey - (:unkn) unknown (CUMHURIYET UNIV TIP FAK PSIKIYATRI ANABILIM DALI, 2018)
Objective: It is well-known that refugee children are under risk of psychiatric problems as a consequence of adverse events experienced in the pre and post-migration period. It is estimated that, as the leading country hosting refugees, approximately 1.4 million refugee children are living in Turkey. This study aimed to evaluate emotional and behavioral problems seen among Yazidi children and adolescents who settle in a refugee camp in Turkey. Methods: The researcher contacted the volunteers of the transient education center situated in the camp and reached children attending the center as well as their families. The emotional and behavioral problems were investigated using Arabic form of Strength and Difficulties Questionnaire (SDQ). Results: Our sample consisted of 33 female and 20 male children and adolescents. The mean age was 12.3 +/- 1.5 years. The mean residency time in camp was 11.3 +/- 2.1 months. The mean number of siblings was 3.9 +/- 1.8. 60.4% of fathers and 67.9% of mothers were primary school graduate or less educated. Majority of the children (88.7%) reported that they lost a relative or could not get any information about at least one of them, 58.0% stated they heard the sound of gunshot or explosion, while 39.6% reported they saw the body of a dead or injured person. SDQ scores were higher than threshold for emotional problem in 26.4%, peer problems in 22.6%, hyperactivity problems in 18.8% and conduct problem in 15.0% of children. Total difficulty scores of 15 (28.3%) children were also higher than cut-off value. Conclusion: Results of the study showed that refugee children and adolescents had exposed to many traumatic events and emotional and behavioral problems might be seen in a significant proportion of this group. It is highly recommended to provide psychosocial support in the help and care programs targeting child and adolescent refugees.
Keywords: refugee; defector; stres; war; Yazidi; Strength and Difficulties Questionnaire; trauma; mental health; MENTAL-HEALTH PROBLEMS; DIFFICULTIES QUESTIONNAIRE; POSTTRAUMATIC-STRESS; TURKISH IMMIGRANT; RISK-FACTORS; DEPRESSION; STRENGTHS; TRAUMA; CARE; PREVALENCE